1998
DOI: 10.1002/jlb.64.6.810
|View full text |Cite
|
Sign up to set email alerts
|

CSF-1 regulation of I6 gene expression by murine macrophages: a pivotal role for GM-CSF

Abstract: We test the hypothesis that the monocyte-macrophage colony-stimulating factor (CSF-1 or M-CSF) plays a major role in the inflammatory responses of M by acting as a priming agent that heightens their responsiveness to secondary stimulation by other mediators. We previously reported that CSF-1 induced peritoneal M (PM ) to transcribe several genes including interleukin-6 (Il6) and granulocyte-macrophage colony-stimulating factor (Csfgm). It was reported that the Il6 and Csfgm genes were individually regulated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Recent data have indicated that CSF-1 drives multiple pathways during the expression of the Il6 gene and is influenced by Csfgm and Tnfa gene expression [4]. To determine if the elevation of IL-6 release by resident PMÊ upon stimulation by the combination of CSF-1 and FN is paralleled in GM-CSF and TNF-· release, resident PMÊ were incubated in 24-well plates coated with FN (10 Ìg/ml) and a fixed concentration of CSF-1 (10 4 U/ml) and culture supernatants were assayed at intervals over 24 h for IL-6, GM-CSF and TNF-·.…”
Section: Csf-1 and Fn Induce Gm-csf And Tnf-· Releasementioning
confidence: 99%
See 4 more Smart Citations
“…Recent data have indicated that CSF-1 drives multiple pathways during the expression of the Il6 gene and is influenced by Csfgm and Tnfa gene expression [4]. To determine if the elevation of IL-6 release by resident PMÊ upon stimulation by the combination of CSF-1 and FN is paralleled in GM-CSF and TNF-· release, resident PMÊ were incubated in 24-well plates coated with FN (10 Ìg/ml) and a fixed concentration of CSF-1 (10 4 U/ml) and culture supernatants were assayed at intervals over 24 h for IL-6, GM-CSF and TNF-·.…”
Section: Csf-1 and Fn Induce Gm-csf And Tnf-· Releasementioning
confidence: 99%
“…Cytokine Enzyme-Linked Immunosorbent Assays IL-6, GM-CSF and TNF-· were assayed by enzyme-linked immunosorbent assays (ELISAs) developed in our laboratory [1][2][3][4]10]. The lower and upper values for the detection of IL-6 were 0.039 and 2.5 ng/ ml.…”
Section: Mononuclear Phagocytementioning
confidence: 99%
See 3 more Smart Citations